Molecular characterization of candidate genes involved in nitrogen metabolism and relationship with the grain protein content of wheat - Gadaleta A.; Nigro D.; Marcotuli I.; Giancaspro A.; Blanco A. (Proceedings of the International Symposium on Genetics and breeding of durum wheat, 2014)
Wheat is one of the most important cereal crops grown worldwide and provides most of the proteins in human diet. Grain protein content (GPC) determines the nutritional value and the baking properties of common wheat (Triticum aestivum L. ssp. aestivum) as well as the pasta-making technology characteristics of durum wheat (Triticum turgidum L. ssp. durum). GPC is a typical quantitative trait controlled by a complex genetic system and influenced by environmental factors and management practices, as well as nitrogen and water availability, temperature and light intensity. In higher plants inorganic nitrogen, in the form of ammonia, is assimilated via the glutamate synthase cycle or GS-GOGAT pathway. This assimilation requires cofactors, reducing equivalents and carbon skeletons generated during photosynthesis. We focused on the Glutamine synthetase and Glutamate synthase, as potential candidates for determining grain protein content. While Glutamine synthetase genes are a family whose enzymes are located in both cytoplasm and plastids, glutamate synthase exists in two different isoform depending on the electron donor used as cofactor, NADH- dependent and Fd- dependent GOGAT, both active in plastids. In the present manuscript has been reported an overview on the candidate gene involved found in the control of grain protein content.
International Symposium : Genetics and Breeding of Durum Wheat, 2013/05/27-30, Rome (Italy)